The megalithic tombs of Southern Beira Interior, Portugal : recent contributions - Cardoso, João Luís (2008)
In this study, we present the main results obtained during the archaeological survey of a vast area south of Beira Interior, in the region of International river Tagus, followed by the excavation of the more representative and best preserved funerary megalithic monuments. In this way, it was possible to identify several types of monuments and to relate these with the artefact findings, and to develop a model to explain the architectonic succession of funerary megalithic monuments in the region. It was also possible to observe some constructive particularities in some of these monuments, and aspects related to the ritual deposition of remains, herein summarized.